INTEGRATING PHOTOBIOREACTORS IN ARCHITECTURE FOR SUSTAINABLE DESIGN AND PERFORMANCE (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Growing threats to the world environment due to climate changes, energy crises, and pollution of the urban areas pose a high degree of urgency to come up with new sustainable architectural solutions. Building-Integrated Photobioreactors (BIPBRs), In which microalgae produce biomass powered by CO 2 and sunlight, have cropped up as an effective solution to increase the sustainability and multifunctional architecture of buildings. There is no research, apart from photobioreactor systems as isolated industrial solutions, and little to say about the practical integration of photobioreactor systems in building facade in diverse climatic environments, mainly its long-term performance, cleaning and environmental modelling. In a critical analysis of the design, classification, performance measures and architectural integrability of BIPBR systems, the analysis in this review evaluates the field of BIPBR systems in an endeavor to embrace all these parameters with the context of productivity, cost-intensiveness and aesthetic feasibility. Results have shown that sophisticated PBR schemes especially helical and hybrid facades are more productive and beneficial in terms of energy production but also at a higher cost and intricacy of construction. A viable trade off is evident in flat panel systems. The paper outlined a full assessment between biological engineering and architecture design with support by comparison data and modeling schemes to direct further development of BIPBR. These findings confirm the use of BIPBRs as an efficient means in green architecture, which helps to build carbon-neutral buildings and have adaptive building systems. Additional interdisciplinary studies will also be required to standardize species choice, control systems in the environment and large scale prototyping to enable long-term deployment of such systems in cities.